Asymmetry in the application of inward ground reaction force during curved sprinting on athletic track - Hirono, Y.; Fujii, N. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
We assessed the factors influencing the application of inward GRF during the left and right contact phases in curved sprinting. This study resulted no significant differences in inward impulse and mean inward GRF between the two contact phases. The symmetry index in inward GRF depended on the magnitude of both inward GRFs during the left and right contact phases. Based on the significant correlation between mean inward GRF and hip abduction torque, we propose that large inward GRF is influenced by the absence of inward pushing during the left contact phase, whereas it is influenced by outward pushing during the right contact phase. The left contact phase seems to involve a shift in the action direction of ankle plantarflexion, as mean inward GRF exhibited a significant correlation with ankle plantarflexion.